POLITIK HUKUM PENGATURAN PENUNJUKAN DATUK ADAT DALAM MASYARAKAT HUKUM ADAT PESUKUAN LUHAK RAMBAH DI KABUPATEN ROKAN HULU - Yuli Hesman; Evi Deliana; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In the election of the traditional datuk in Luhak Rambah, there is an arrangement inthe form of appointment. However, in this case, conflicts and controversies often occurbetween the children and nephews of tribal groups. Therefore, this research aims to find outthe electoral system, traditional leadership structure in Luhak Rambah, and so on. This iswhat ideally happens in the Luhak Rambah community and this research can be used as areference in making a policy. So, from this research, it was found that, in the legal system forthe election of traditional datuks in the customary law community of the Luhak Rambah tribe,the election was carried out due to several factors.The first was that the replacement of the dila was due to the condition of thetraditional datuk (age and illness), so the election was carried out by means of deliberationand an appointment process. /appointed in accordance with the order of descent of thenephew's children. Second, the election is because the traditional datuk dies, so the electionis carried out by determining which nephew's son will hold the body of the grandfather forthe first time (cleaning the genitals), then that is the person who will be appointed to be thedatuk next custom. From this research, ideas/mechanisms and more relevant regulationsfrom the government are needed as guidelines and implementation rules to overcomeproblems that have occurred so that they do not happen again and can be carried outaccording to existing customs.Keywords : Electoral System, Customs, Tribal People, Luhak Rambah